Knowledge, attitudes and practices of pain management among Taiwanese physicians in a reformed 2-year postgraduate training programme: a cross-sectional questionnaire survey - Jia-Lin Chen; Shung-Tai Ho; Chun-Chang Yeh; Chi-Wei Feng; Che-Hao Hsu; Tso-Chou Lin (Annals of Medicine, 2025)
Background Taiwan implemented a reformed 6-year medical education in 2013, with a subsequent 2-year postgraduate training programme starting in August 2019. This study investigated the perceptions of acute and chronic pain management in postgraduate physicians.Methods In late July 2023, a cross-sectional questionnaire survey was conducted of Taiwanese physicians who had almost completed their postgraduate 2-year or 1-year training and those who were starting a postgraduate programme in early August 2023. This survey evaluated their knowledge, attitude and clinical experience related to opioid-based pain management and their perceptions of the opioid crisis in the United States and Taiwan.Results Of the 197 postgraduate physicians, 169 (85.8%) responded to the survey. Physicians who had received postgraduate 2-year (n = 48) and 1-year (n = 51) training had a deeper understanding of opioids (p < 0.001) and exhibited greater confidence in acute and chronic pain management (both p < 0.001) compared with those who were just starting a postgraduate programme (n = 70). Of the included physicians, 92 (54.4%) were aware of the ongoing opioid crisis in the United States, but only 28 (16.6%) disagreed with the notion of a current opioid problem in Taiwan. Approximately 27.8% had never heard of multimodal analgesia, and 86.4% expressed a need for further pain management education.Conclusions The postgraduate training programme in Taiwan provides enhanced knowledge of opioids and improves physicians’ levels of confidence in acute and chronic pain management. However, only one-sixth of postgraduate physicians are aware that Taiwan does not have an opioid problem.